Analysis of the Effectiveness of Instilling Islamic Religious Values in Shaping Students' Religious Character - Maulana, Hasan; Budiana, Irma; Adih, Adih; Hayatina, Lamya; Abnisa, Almaydza Pratama (STAI Publisistik Thawalib Jakarta, 2025)
Religious character education in Madrasah Aliyah plays a crucial role in fostering students with integrity through the integration of Islamic values, exemplary behaviour by teachers, and collaboration among all stakeholders. This study aims to assess the impact of systematically instilling Islamic values on the development of religious character among 10th-grade students at a private Madrasah Aliyah. Employing a quantitative approach with a one-group pretest-posttest design involving 30 students, data were collected through questionnaires and observations, and subsequently analysed using SPSS statistical tests. The results indicate that the data are valid, with all significance values (Sig.) below 0.01, signifying a strong correlation between the indicators and the total score. The normality test yielded Sig. Values above 0.05 indicate a normal data distribution and eligibility for parametric testing. The t-test resulted in a t-value of 4.011, exceeding the t-table value of 2.045 (df = 29), with a Sig. Value of 0.000 < 0.05, suggesting a significant difference in students’ religious character before and after the treatment. An R-squared value of 36.5% demonstrates that the treatment significantly and substantially explains the change in students' religious character. Conclusion: The systematic integration of Islamic religious values through religious activities and curriculum integration effectively shapes students' religious character, reflected in consistent religious understanding, attitudes, and behaviour.